Child Soldiers: victims or perpetrators - how they are treated under international law and Sierra Leonean law - Baader, Philine (Department of Public Law, 2023)
Archbishop Desmond Tutu once said: 'We must not close our eyes to the fact that child soldiers are both victims and perpetrators. They sometimes carry out the most barbaric acts of violence. But no matter what the child is guilty of, the main responsibility lies with us, the adults. There is simply no excuse, no acceptable argument for arming children'.